110=12+6t

Simple and best practice solution for 110=12+6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 110=12+6t equation:


Simplifying
110 = 12 + 6t

Solving
110 = 12 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
110 + -6t = 12 + 6t + -6t

Combine like terms: 6t + -6t = 0
110 + -6t = 12 + 0
110 + -6t = 12

Add '-110' to each side of the equation.
110 + -110 + -6t = 12 + -110

Combine like terms: 110 + -110 = 0
0 + -6t = 12 + -110
-6t = 12 + -110

Combine like terms: 12 + -110 = -98
-6t = -98

Divide each side by '-6'.
t = 16.33333333

Simplifying
t = 16.33333333

See similar equations:

| 6-(2x-1)=5(3x-4) | | 6+3k=6+2k | | 30x+35y=58450 | | -9/8=8/1 | | y=-3.8x+4.8 | | w-2(8-w)=31 | | 106=4r+2d | | 2x-19+1=0 | | 30x+35y=49233 | | 0=36x^2+12x-6 | | 2x-2.19=0 | | 6x-2=-3 | | 5(2x-1)+6=5(x+2)-9 | | 2(5t-2)=-4[2t+5(t-10)] | | 8q-(5q-7)= | | 10x-1+6=5x+2-9 | | 30x+35y=52750 | | (7v-4x+2)(v-7)= | | 6(3x^2+5x-2)+3x^2-4=0 | | 30(5x)=6x | | y=60-30x | | 0.09Xx=112.33 | | 30x+35y=51000 | | 5(4x)=3x+4(6-x) | | (9x-7)(x+4)= | | z^3+iz^2-iz+1=0 | | xa-19=0 | | -40=7y-3x | | 1/4y=x | | 3/4=n/75 | | Cos(2x)+cos(x)=9 | | 0.04p+48=p |

Equations solver categories